Identification and Validation of Ferroptosis-Related Subtypes and a Predictive Signature in Hepatocellular Carcinoma - Zheng C; Peng Y; Wang H; Wang Y; Liu L; Zhao Q (Dove Medical Press, 2023)
Chunlan Zheng,1,2,* Yanan Peng,1,2,* Haizhou Wang,1,2 Youwei Wang,1,2 Lan Liu,1,2,* Qiu Zhao1,2,* 1Department of Gastroenterology, Zhongnan Hospital of Wuhan University, Wuhan, 430071, People's Republic of China; 2Hubei Clinical Center and Key Laboratory of Intestinal and Colorectal Diseases, Wuhan, 430071, People's Republic of China*These authors contributed equally to this workCorrespondence: Lan Liu; Qiu Zhao, Tel +86-027-67812888, Fax +86 027-67812892, Email lliugi@whu.edu.cn; qiuzhao@whu.edu.cnBackground: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world with an immunosuppressive Tumor microenvironment (TME). Ferroptosis plays an essential role in tumor proliferation, invasion, and metastasis. However, the relationship between ferroptosis and TME of HCC has remained elusive.Methods: Differentially expressed ferroptosis-related genes (DE FRGs) between normal liver tissues and HCC tissues were obtained from The Cancer Genome Atlas (TCGA). On this basis, we identified the molecular subtypes mediated by DE FRGs and TME cell infiltration. Next, a predictive signature was established to quantity the ferroptosis-related characteristics by performing the least absolute shrinkage and selection operator Cox regression analyses. Univariate and multivariate COX analyses determined the independent prognostic factors. Finally, the expression stability of 3 ferroptosis-related signature genes was verified in cancer and paracancerous normal tissues of HCC.Results: We identified three different molecular subtypes and found that the subtype with the better prognosis was associated with high enrichment of immune- and metabolic-related hallmark signaling pathways and high infiltration of immune cells in TME. The signature was considered to be an independent prognostic factor. We also found that the signature can reflect the infiltration characteristics of different immune cells in TME. Immunosuppressive cells such as myeloid-derived suppressor cells (MDSCs), regulatory T cells, and type 17 T helper cells were significantly enriched in the high-risk group. The analysis data of immune checkpoints and tumor mutation load indicated that the signature had great potential in predicting Immunotherapy response and chemotherapeutic sensitivity. In addition, the overexpression of 3 ferroptosis-related signature genes was confirmed in HCC tissues and HCC cell lines. Ferroptosis inducer RSL3 inhibited the proliferation of HCC cells and was a potential cancer immunotherapy agent.Conclusion: These findings enhanced our understanding of the regulatory mechanism of ferroptosis in HCC and provided new insights into evaluating prognosis and developing more effective Immunotherapy and chemotherapy strategies.Keywords: hepatocellular carcinoma, ferroptosis, prognosis, immunotherapy, tumor mutational burden